Nell's Story : A Woman from Eagle River - Peters, Nell, 1932-; Peters, Robert, 1924-2014 (Book collections on Project MUSE., 1995)
The year was 1951, and Nell Peters, just out of high school in the north woods of Wisconsin, was about to join the army. Feeling woefully unworldly, she asked the undertaker's grandson to initiate her into sex before she ventured off. She wasn't in the WACs long before she found herself pregnant and heading home to face the kind of adventure she hadn't looked for. An outrageous fortune, but of a piece with Nell's whole story, from her harrowing birth in a snowstorm to her current occupation running a perpetual garage sale to benefit disabled veterans. Sometimes funny, sometimes gritty, always wildly candid and sexual, this is a remarkable account of a woman's life lived in extremity.